Ultrasound Scanning in Infants with Biliary Atresia: The Different Implications of Biliary Tract Features and Liver Echostructure - Iorio, R.; Liccardo, D.; Di Dato, F.; Puoti, M. G.; Spagnuolo, M. I.; Alberti, D.; Vallone, G. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Objective: To evaluate ultrasonographic features of the liver and biliary tree, including the presence of the triangular cord, in infants with biliary atresia and to analyze the correspondence between hepatic echostructure and histological aspects of the liver.Materials and Methods: 35 consecutive infants (19 males) with documented diagnosis of biliary atresia were included. Ultrasonography evaluation, performed at a mean age of 63.1 ± 34.9 days, was focused on the extrahepatic bile ducts, characteristics of the gallbladder and liver, and the presence of the triangular cord. Liver biopsies were examined with particular regard to the presence and severity of fibrosis.Results: On ultrasound, the gallbladder was not seen in 11 (31 %) cases, while in the remaining 24 patients the gallbladder was regular in 6 patients and irregular in 18 cases. The triangular cord was identified in 9 (26 %) of 35 patients. In 21 patients the liver echostructure appeared normal, while in 14 infants the liver parenchyma was more echogenic and coarse than normal. Liver biopsy showed signs of cirrhosis or fibrosis in all cases, including patients with a normal hepatic echostructure.Conclusion: Although the triangular cord was visualized in one-fourth of the infants with biliary atresia, abnormalities of the gallbladder on ultrasound (absence or abnormalities of length/shape) were detected in 83 % of the patients. Therefore, ultrasound evaluation of the liver and biliary tree plays an important role in suspecting biliary atresia. On the other hand, a low correspondence between liver echostructure aspects and the presence and severity of fibrosis at liver biopsy was identified. Therefore, severe liver disease in infants with biliary atresia cannot be excluded only on the basis of ultrasound findings.
Keywords: biliary atresia; ultrasonography; triangular cord